Primary Care Diagnosis and Treatment of Attention-Deficit/Hyperactivity Disorder in School-Age Children: Trends and Disparities During the COVID-19 Pandemic. Issue 7 (2nd September 2022) - Bannett, Yair; Dahlen, Alex; Huffman, Lynne C.; Feldman, Heidi M.
Abstract : This article has supplementary material on the web site: www.jdbp.org . ABSTRACT: Objective: The aim of this study was to assess rates of primary care provider (PCP) diagnosis and treatment of school-age children with attention-deficit/hyperactivity disorder (ADHD) during the COVID-19 pandemic compared with prepandemic years and to investigate disparities in care. Method: We retrospectively analyzed electronic health records from all primary care visits (in-person and telehealth) of children aged 6 to 17 years seen between January 2016 and March 2021 in a community-based primary health care network (n = 77, 298 patients). Study outcomes are as follows: (1) number of primary care visits, (2) number of visits with ADHD diagnosis (ADHD-related visits), (3) number of PCP prescriptions for ADHD medications, (4) number of patients with first ADHD diagnoses, and (5) number of first PCP prescriptions of ADHD medications. Interrupted time series analysis evaluated changes in rates of study outcomes during 4 quarters of the pandemic year (March 15, 2020–March 15, 2021) compared with prepandemic years (January 1, 2016–March 14, 2020). Patient demographic characteristics during prepandemic and pandemic years were compared. Results: ADHD–related visits dropped in the first quarter of the pandemic year by 33% (95% confidence interval, 22.2%–43.6%), returning to prepandemic rates in subsequent quarters. ADHD medication prescription rates remained stable throughout the pandemic year. Conversely, rates of first ADHD diagnoses and first medication prescriptions remained significantly lower than prepandemic rates. The proportion of ADHD-related visits for patients living in low-income neighborhoods was lower in the pandemic year compared with prepandemic years. Conclusion: Ongoing treatment for school-age children with ADHD was maintained during the pandemic, especially in high-income families. Socioeconomic differences in ADHD-related care emphasize the need to improve access to care for all children with ADHD in the ongoing pandemic and beyond.